Perbandingan Penerapan PSAK 210 Perusahaan Penerbangan BUMN dan Swasta di Indonesia Tahun 2021-2024 - Juliono, Sigit; Mais, Rimi Gusliana (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2025)
This study aims to analyze and compare the application of the Financial Accounting Standard (PSAK) 8 (now known as PSAK 210) regarding events after the reporting period in state-owned and private airline companies in Indonesia during the 2021–2024 period. The primary focus is on the classification of adjusting and non-adjusting events, the quality of disclosures, and the level of compliance with the standards. This study uses a descriptive-qualitative approach with content analysis of the financial reports of PT Garuda Indonesia (Persero) Tbk as a representation of state-owned enterprises (SOEs) and PT AirAsia Indonesia Tbk as a private company. The results show that Garuda Indonesia implemented PSAK 210 more openly and comprehensively compared to AirAsia Indonesia, which tended to be selective in its disclosures. These differences are influenced by ownership structure, regulatory pressure, and public accountability demands. This research contributes to understanding accounting practices in crisis situations and suggests the need for more detailed disclosure guidelines, especially for strategic sectors such as the aviation industry.